2019
DOI: 10.1029/2018ja026259
|View full text |Cite
|
Sign up to set email alerts
|

Multiyear Measurements of Radiation Belt Electrons: Acceleration, Transport, and Loss

Abstract: In addition to clarifying morphological structures of the Earth's radiation belts, it has also been a major achievement of the Van Allen Probes mission to understand more thoroughly how highly relativistic and ultrarelativistic electrons are accelerated deep inside the radiation belts. Prior studies have demonstrated that electrons up to energies of 10 megaelectron volts (MeV) can be produced over broad regions of the outer Van Allen zone on timescales of minutes to a few hours. It often is seen that geomagnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 39 publications
6
66
0
Order By: Relevance
“…The difference in performance can be explained by the fact that a much larger training set incorporate a wider flux variation that can be helpful to train the models. Besides, the addition of SW speeds definitely helps improve the performance of linear models at large L‐shells, which is consistent with Baker et al's study (Baker et al, ) that confirms the importance of solar wind speeds for MeV electron flux levels.…”
Section: Detailed Predictions and Discussionsupporting
confidence: 88%
“…The difference in performance can be explained by the fact that a much larger training set incorporate a wider flux variation that can be helpful to train the models. Besides, the addition of SW speeds definitely helps improve the performance of linear models at large L‐shells, which is consistent with Baker et al's study (Baker et al, ) that confirms the importance of solar wind speeds for MeV electron flux levels.…”
Section: Detailed Predictions and Discussionsupporting
confidence: 88%
“…The initial trapped electron level varies for the year investigated. The trapped flux level is especially low in the year 2014 compared to other periods (Baker et al, ) when recurrent high‐speed solar wind streams that are favorable for accelerating electrons (Baker et al, ; Li et al, ; McPherron et al, ) are frequently observed. The number of conjunction events, coincidence events and coincidence occurrence rate for each year are shown in Table .…”
Section: Statistical Resultsmentioning
confidence: 99%
“…The large number of the transient extensions indicates that they are caused by dynamic processes that are common for the Saturnian magnetosphere and are efficient in accelerating electrons to MeV energies. Note that the variability of Earth's electron belts is also very significant (e.g., Baker et al, ), even though the triggers might be different (Ma et al, ; Turner et al, ; Yuan & Zong, , ). Whereas, the proton belts of both planets are relatively less dynamic than their electron counterparts (Kollmann et al, ).…”
Section: Discussionmentioning
confidence: 99%